2023
DOI: 10.3390/ijerph20075425
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Investigation of Facilitators to Accessing and Utilising Mental Health Services amongst Sri Lankan Australians

Abstract: Many individuals with mental health conditions avoid, delay, discontinue, or do not seek mental health services and treatments, despite the existence of evidence-based treatments and support methods. Little is known about the barriers to mental health service utilisation for Sri Lankan Australians, and there is no research on factors that facilitate access for this group. Using quantitative and qualitative methods, this study explored the perspectives of Sri Lankan Australians (N = 262) on the facilitators of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The attitudes of mental health professionals towards mental illness can hinder the recovery of PMI [ 15 ]. Conversely, establishing a positive relationship with mental health professionals can significantly enhance patients' willingness to seek and use mental health services [ 16 ]. Studies have shown that mental health nurses' attitudes toward mental illness mirror those of the general public, exhibiting more negative attitudes toward patients with schizophrenia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The attitudes of mental health professionals towards mental illness can hinder the recovery of PMI [ 15 ]. Conversely, establishing a positive relationship with mental health professionals can significantly enhance patients' willingness to seek and use mental health services [ 16 ]. Studies have shown that mental health nurses' attitudes toward mental illness mirror those of the general public, exhibiting more negative attitudes toward patients with schizophrenia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%